Being and existence in Kierkegaard's pseudonymous works - Elrod, John W. (William), 1940-2001 (Princeton legacy library., 1975)
In this study John W. Elrod demonstrates that Kierkegaard's pseudonymous writings have an ontological foundation that unites the disparate elements of these books. The descriptions of the different stages of human development are not fully understandable, the author argues, without an awareness of the role played by this ontology in Kierkegaard's analysis of human existence. Kierkegaard contends that the self is a synthesis of finitude and infinitude, body and soul, reality and ideality, necessity and possibility, and time and eternity. Each of these syntheses reveals a particular and unique.